Influence of parameters and radical scavengers on the visible-light-induced degradation of ciprofloxacin in ZnO/SnS 2 nanocomposite suspension: Identification of transformation products - Makama, Abdullahi B.; Ali, Salmiaton; Choong, Thomas Shean Yaw; Abdul Hamid, Mohamad Rezi; Abdullah, Norhafizah; Saion, Elias (Elsevier, 2020)
Removal of ciprofloxacin (CIP) pollutant from wastewater using conventional process is particularly challenging due to poor removal efficiency. In this work, CIP was photocatalytically degraded using a porous ZnO/SnS2 photocatalyst prepared via microwaves. The influence of process parameters (e.g., pH, catalyst mass and initial CIP concentration) and radical scavengers on visible-light induced degradation of CIP on the catalyst was investigated. From the study, it was found that visible-light induced degradation of CIP on ZnO/SnS2 is a surface-mediated process and the reaction kinetics followed the Langmuir-Hinshelwood first-order kinetics. It was found that the optimum condition for CIP degradation was at pH of 6.1 and catalyst dosage of 500 mg L−1. Higher catalyst dosage however led to a decline in reaction rate due to light scattering effect and reduction in light penetration.